Local adaptation in natural European host grass populations with asymmetric symbiosis - Leinonen P.; Helander M.; Vázquez-De-Aldana B.; Zabalgogeazcoa I.; Saikkonen K. (Public Library of Science, 2022)
Recent work on microbiomes is revealing the wealth and importance of plant-microbe interactions. Microbial symbionts are proposed to have profound effects on fitness of their host plants and vice versa, especially when their fitness is tightly linked. Here we studied local adaptation of host plants and possible fitness contribution of such symbiosis in the context of abiotic environmental factors. We conducted a four-way multi-year reciprocal transplant experiment with natural populations of the perennial grass Festuca rubra s.l. from northern and southern Finland, Faroe Islands and Spain. We included F. rubra with and without transmitted symbiotic fungus Epichloë that is vertically transmitted via host seed. We found local adaptation across the European range, as evidenced by higher host fitness of the local geographic origin compared with nonlocals at three of the four studied sites, suggesting that selection pressures are driving evolution in different directions. Abiotic factors did not result in strong fitness effects related to Epichloë symbiosis, indicating that other factors such as herbivory are more likely to contribute to fitness differences between plants naturally occurring with or without Epichloë. Nevertheless, in the case of asymmetric symbiosis that is obligatory for the symbiont, abiotic conditions that affect performance of the host, may also cause selective pressure for the symbiont.